Pengaruh Penggunaan Gadget terhadap Perilaku Seksual Remaja - Lela Zakiah; Shanti Ariandini; Marsanda Syalum Juliani; Riski Septiani; Siti Sumayah; Sri Dina (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
In the era of modern technology, the use of gadgets among teenagers continues to rise, particularly for accessing social media, which can influence their behavior, including sexual behavior. This study aims to examine the impact of gadget use on adolescent sexual behavior. The research approach is quantitative, using an analytic survey method with a cross-sectional design. The study sample consists of 94 twelfth-grade students selected through total sampling. The variables studied include gadget use as the independent variable and adolescent sexual behavior as the dependent variable, measured using a closed-ended questionnaire. The results indicate that 89 respondents (94.7%) reported high levels of gadget use. Furthermore, 70 respondents (74.5%) exhibited risky sexual behavior. The Chi-Square statistical test with a p-value of 0.004 and an OR of 13.800 shows a significant relationship between gadget use and adolescent sexual behavior. These findings suggest that excessive gadget use can increase the risk of sexual behavior among teenagers. Therefore, this study is expected to help prevent such behavior through stricter supervision, appropriate sex education, and the active role of parents and schools in guiding teenagers to use gadgets safely.